Olympic sponsorship to China's entrepreneurs: Pie or pit - Yu, L.; Cao, K. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Facing the competitive and developing marketing environment, entrepreneurs are now becoming much more rational. Masses of data provided on Olympic sponsorship indicates that large-scale funding of the Olympics is becoming less efficient for the promotion of companies. Domestically, and internationally, a growing number of large companies who traditionally spend substantial amounts to associate their brands with the image and idea of the Olympic Game are questioning these actions. This work focused on the issue of current developments of domestic sponsors` strategies with some examples, and discusses both theoretical and practical ways to ensure the further effectiveness and attractiveness of their efforts. Methods The issue was discussed both theoretically and practically, mainly using qualitative analysis, including several phases. The first phase involved discovering this question using consultations with experienced specialists in marketing and sports economics to define research problems and possible courses of action. The secondary phase involved an in-depth review of historical and current documents in related areas. The third phase involved detailed discussion combining domestic sponsors` practice the 2008 Olympic Game with former research experience. Results According to an ongoing investigation of Ipsos China, 63% of Chinese people confuse sponsors with non-sponsors, which mean domestic sponsors still need further development. There are many successful enterprises in sports marketing including sponsorship such as NongFu Spring, a once small, private enterprise. Meanwhile, there was more consideration when Lenovo announced their desire to leave the Olympic Program after the 2008 Olympic Game. Discussion / Conclusions Companies have to decide on the corporate expectations of sponsoring the Olympics. Both corporaterelated objectives and product brand-related objectives should be considered. The former may include increasing public awareness of the organization and altering public perception while the latter may include brand preference and increased sales and increasing target market awareness. Domestic sponsors may adopt the Resource Based View to further understanding the sponsorship management nd implementation processes. The resources analysis includes intangible assets such as market oriented behaviors, brand building skills and collaborative communication, especially, those large-scale state-owned enterprises with monopoly power such as China Mobile, CNC, CNPC and Sinopec. .Integrated marketing is known to be an indispensable tool, while offering experience for customers may be an ignored key for domestic sponsors.